Delayed Asthmatic Response to Allergen Challenge and Cytokines Released by Nonspecifically Stimulated Blood Cells. (13th February 2013) - Pelikan, Zdenek
Abstract : Background . Bronchial asthma patients can develop various asthmatic response types following bronchial allergen challenge, such as immediate (IAR), late (LAR), dual late (DLAR), or delayed (DYAR), due to different immunologic mechanisms. The DYAR, recorded in 24 patients, beginning between 26 and 32 hrs and lasting up to 56 hrs after the bronchial allergen challenge, differs from the IAR, LAR, and DLAR in clinical, diagnostic, and immunologic aspects. Objective . To investigate amounts of particular cytokines released by the blood cells after an additional nonspecific stimulation with Phorbol 12-myristate 13-acetate (PMA) during the DYAR. Methods . In 24 patients, the repeated DYAR was supplemented with determination of cytokines both in the nonstimulated plasma and in the supernatants of the blood cells stimulated with PMA before and up to 72 hours after the bronchial challenge, by means of enzyme-linked immunoassay. Results . No significant changes of the prechallenge cytokine concentrations in the non-stimulated serum were recorded in the DYAR patients as compared with the healthy subjects. The DYAR was accompanied by significantly increased postchallenge concentrations (P < 0 .05 ) of IL-2, IL-8, IL-12p70, IL-13, IL-18, IFN- γ, G-CSF, TNF- α, and TGF- β, while decreased concentration of IL-7 (P < 0 .05 ) in the nonstimulated plasma. The significantly increased postchallenge concentrations of IL-2, IL-8, IL-12p70, IL-13, IL-18, IFN- γ, TNF- α, and TGF- β were released by peripheral blood cells after stimulation with PMA, as compared with both their prechallenge concentrations and with the PBS control values. Conclusions . These results would support evidence for an important role of the Th1 cells, neutrophils, monocytes, and probably also NK cells in the immunologic mechanism(s) leading to the development of the clinical DYAR. Nevertheless, an additional role of macrophages, endothelial and epithelial cells in these mechanisms cannot be even excluded.